About the challenged notion of "Curve of a City". The example of the pilgrimage of Lourdes (France). - Lefebvre, Olivier (My University, 2017)
The French urban planner Marcel Poëte set out the notions of "city's curve" and "mysticism" of the city (around the 20s). The city's curve is the history of the city: in general, there is the beneficial influence of some power, during a long time. And the "mysticism" is when the values of the city are displayed by monuments everywhere. These notions are no more valid. Today the success of a city depends on good governance: the city has to play games in a better way than the rival cities. And the rules of the games are the same everywhere. The "mysticism" is no more fashionable because of two phenomena: (1) the artifying of cities (2) what we call the "meaningless and seductive city", referring to the works of Baudrillard (according to him, the disappearance of sense triggers "cool seduction"). Lourdes is an interesting example: the city's curve perfectly explains the past of this city, but not the present. We conclude examining the consequences of the two phenomena concerning these topics: · How the artified center of the large cities is fashioned by diverse "historical styles"; "Airbnbizing" of some cities in southern Europe.
Keywords: Stadtsoziologie; Historische Stadt; Wallfahrtsort; Stadtgestalt; Stadtbild; Stadtgeschichte; Stadtraum; Bedeutungswandel; Strukturwandel